Architectural Approaches for Self-Healing Systems Based on Multi Agent Technologies - Hamid Bagheri; Mohammad Ali Torkamani; Zhaleh Ghaffari (Institute of Advanced Engineering and Science, 2013)
Self-healing systems are able to adapt themselves at runtime time in response to changing environmental or operational circumstances, shifting user requirements, and unanticipated faults without human intervention. Conceptually, a self-managing system is composed of four key capabilities; Monitoring, performing Analysis, Planning and Executing the plan. The preferred way to enable repair in a self-healing system is to use externalized repair/adaptation architecture. Adaptability, dynamicity, awareness, observability, autonomy, robustness, distributability, mobility and traceability are requirements that an architecture style for self-healing system should satisfy. In this paper we discuss Multi agent based self-healing system has a characteristics that can satisfy mentioned requirement. We define associations between architecture style requirements for self-healing system and MAS characteristics. As a case study in a real project we have designed Automated Teller Machine (ATM) combination with biometric sensors based on multi-agent architecture.DOI:http://dx.doi.org/10.11591/ijece.v3i6.3952